Brucella canis Group 2 isolated in Argentina = Brucella canis Grupo 2 aislado en Argentina - Boeri, Eduardo Jorge; Madariaga, María Julia; Dominguez, María Luz; Teijeiro, María Luisa; Fernandez, Natalia Mercedes; Elena, Sebastián Alejandro; Trangoni, Marcos David (Elsevier, 2023)
The aim of this study was to estimate the diversity and prevalence of both groups of Brucella canis 1 and 2 with and without deletion respectively in different areas of Argentina. A total of 104 bacterial cultures were typed as B. canis strains using the classical biotyping method. Two PCR assays were performed to confirm that all isolates were B. canis and not Brucella suis. The differentiation between groups 1 and 2 was achieved using another PCR assay and the diversity of B. canis isolates was assessed with four MLVA_16 markers. All strains belonged to Group 2. Bruce 09 marker (MLVA_16 assay) showed the greatest diversity. Only Group 2 of B. canis was identified among the strains evaluated. The markers chosen from the MLVA_16 allowed us to detect genetic diversity among the strains of B. canis studied.